Pattern recognition Chinese conference, CCPR 2012, Beijing, China, September 24-26, 2012. Proceedings - Zhang, Changshui; Wang, Liang; Liu, Cheng-Lin (Communications in Computer and Information Science, 2012)
This book constitutes the refereed proceedings of the Chinese Conference on Pattern Recognition, CCPR 2012, held in Beijing, China, in September 2012. The 82 revised full papers presented were carefully reviewed and selected from 137 submissions. The papers are organized in topical sections on pattern recognition theory; computer vision; biometric recognition; medical imaging; image and video analysis; document analysis; speech processing; natural language processing and information retrieval.